Occurrence of depression, anxiety and stress among medical students working during COVID Pandemic - Halvadia, Devanshee R.; Bhavsar, Harsh J.; Suthar, Karan M.; Dumra, Gurusharan H.; Patel, Mayank J. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Since the COVID-19 pandemic began, medical students have been allotted various duties like rapid antigen testing, Sanjivani corona ghar seva (service provided by the government for home quarantine people), RTPCR swab collection, and posting in wards and intensive care units (ICUs). While executing the COVID-19 duties, students had a significant degree of a significant degree of ambiguity and apprehension. The purpose of this study was to determine the psychological impact of COVID-19 on medical students performing COVID-19 duties. Methods: A questionnaire-based, cross-sectional observational study was conducted among undergraduate and postgraduate students of a tertiary care teaching hospital, who were deployed on COVID-19 duty during pandemic. A google form-based questionnaire was structured, encompassing demographic details, Depression, Anxiety and Stress Scale-21 (DASS-21) questionnaire and other (additional) COVID-19 duty related questions. The analysis of data was done by using unpaired t-test and chi-square test in Statistical package for social sciences (SPSS) version 20.0 Results: In our research study, we found that occurrence of depression, anxiety, and stress was 40.46%, 48.37%, and 30.69% among the medical students during COVID -19 duty, respectively. Higher occurrence and more severity (p<0.01) of depression, anxiety and stress was seen in female medical students during COVID-19 duty in pandemic. Conclusions: We observed a higher occurrence of depression, anxiety, and stress among medical students while performing their COVID-19 duty in a pandemic. Medical students played a significant role in the COVID-19 pandemic. Therefore, measures should be taken to ensure the psychological wellbeing of medical students.